Supratentorial cerebrospinal fluid diversion using image-guided trigonal ventriculostomy during retrosigmoid craniotomy for cerebellopontine angle tumors - Roethlisberger, Michel; Eberhard, Noëmi Elisabeth; Rychen, Jonathan; Al-Zahid, Saif; Jayapalan, Ronie Romelean; Zweifel, Christian; Karuppiah, Ravindran; Waran, Vicknes (Frontiers in Surgery, 2023)
Background: Cerebellar herniation is often encountered upon durotomy in patients undergoing retrosigmoid craniotomy for cerebellopontine angle (CPA) tumors, despite using standard methods to obtain adequate cerebellar relaxation. Objective: The aim of this study is to report an alternative cerebrospinal fluid (CSF)-diversion method using image-guided ipsilateral trigonal ventriculostomy. Methods: Single-center retro- and prospective cohort study of n=62 patients undergoing above-mentioned technique. Prior durotomy, CSF-diversion was performed to the point where the posterior fossa dura was visibly pulsatile. Outcome assessment consisted of the surgeon’s intra- and postoperative clinical observations, and postoperative radiological imaging. Results: Fifty-two out of n=62 (84%) cases were eligible for analysis. The surgeons consistently reported successful ventricular puncture and a pulsatile dura prior durotomy without cerebellar herniation in n=51/52 (98%) cases. Forty-nine out of n=52 (94%) catheters were placed correctly within the first attempt, with the majority of catheter tips (n=50, 96%) being intraventricular (grade 1 or 2). In n=4/52 (8%) patients, postoperative imaging revealed evidence of a ventriculostomy-related hemorrhage (VRH) associated with an intracerebral hemorrhage (n=2/52 [4%]) or an isolated intraventricular hemorrhage (n=2/52 [4%]). However, these hemorrhagic complications were not associated with neurological symptoms, surgical interventions or postoperative hydrocephalus. In follow-up MRI, supratentorial cortical scars were seen in n=15/52 cases (29%), n=7/52 (13%) of which were associated with a VRH. None of the evaluated patients demonstrated radiological signs of upward herniation. Conclusion: The method described above efficiently allows CSF-diversion prior durotomy during retrosigmoid approach for CPA tumors. However, there is an inherent risk of subclinical supratentorial hemorrhagic complications.